Know Your Library Users: How Three Generations Use Digital Tech. Issue 1 (2nd January 2019) - A. Becker, Danielle
Abstract: To better serve their users, libraries and medical librarians need to be aware of the differences among the three main generations of library patrons: Baby Boomers, Gen Xers, and Millennials. It has been proven that each generation has its own information-seeking preferences, behaviors, and backgrounds. The key to serving each group most effectively is to become knowledgeable about its characteristics, how it approaches and adapts to new technologies, and the most effective ways to communicate with each group. Gaining insight into different generations has implications for library marketing and collection development.